‘Missing links’ alive? Novel taxa represent morphological transitions between distinctive phenotypes among extant Graphidaceae (lichenized Ascomycota: Ostropales) - Kalb, Jutarat; Polyiam, Wetchasart; Plata, Eimy Rivas; Bawingan, Paulina A.; Kalb, Klaus; Lücking, Robert (Phytotaxa, 2016)
We provide an updated account on the species of the Cruentotrema-Dyplolabia clade in Graphidaceae subfamily Fissurinoideae, describing three new species: Cruentotrema lirelliforme J. Kalb, Polyiam & K. Kalb, differing from Cruentotrema thailandicum in the lirelliform ascomata; Dyplolabia chumphonensis J. Kalb & K. Kalb, differing from Dyplolabia oryzoides by smaller ascospores; and Dyplolabia dalywaiana Rivas Plata, Bawingan & Lücking, differing from other Dyplolabia species in the angular, erumpent asomata with broadly exposed disc and irregular pseudocolumella. In addition, two further species are recognized as new combinations: Cruentotrema puniceum (Müll. Arg.) J. Kalb & K. Kalb (Bas.: Arthothelium puniceum Müll. Arg.; syn.: Thelotrema rhododiscum Homchant. & Coppins) and Dyplolabia ochrocheila (Vain.) Rivas Plata & Lücking (Bas.: Graphis ochrocheila Vain.). Cruentotrema kurandense is reported as new to Thailand. Altogether, 11 species are now recognized in the two genera, six in Cruentotrema and five in Dyplolabia. In view of the disparate morphology of the two genera, the discovery of two of the three new species is highlighted as phenotypically transitional taxa, so-called ‘missing links’, and the phylogeny of this clade is revised.